2018
DOI: 10.14202/ijoh.2018.35-39
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rose bengal plate test, serum agglutination test, and indirect enzyme-linked immunosorbent assay in brucellosis detection for human and goat samples

Abstract: Background: In Uganda, detection of brucellosis in goats and humans is more frequently done using rose bengal plate test (RBPT) in comparison to other serological tests such as serum agglutination test (SAT) and indirect enzyme-linked immunosorbent assay (i-ELISA). Aim:This study aimed at estimating the degree of agreement, specificity and sensitivity of RBPT, SAT, and ELISA in brucellosis detection in human and goat samples.Materials and Methods: An analytical study was conducted involving parallel testing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…3 Also, the basic RBT is extremely sensitive but heterospecific 16 ; infection caused by bacteria such as Vibrio cholerae , Yersinia enterocolitica 0:9, Pasteurella spp., Salmonella spp., or some other members of the Brucellaceae family could give more false-positive results in RBT than in the iELISA, a test that may eliminate heterospecific agglutination. The difference in our study results and those reported elsewhere 6,13 could be the result of the difference in the method of the RBT used; we based our results on a mRBT, which is more accurate than the basic RBT when testing small ruminants.…”
contrasting
confidence: 74%
See 4 more Smart Citations
“…3 Also, the basic RBT is extremely sensitive but heterospecific 16 ; infection caused by bacteria such as Vibrio cholerae , Yersinia enterocolitica 0:9, Pasteurella spp., Salmonella spp., or some other members of the Brucellaceae family could give more false-positive results in RBT than in the iELISA, a test that may eliminate heterospecific agglutination. The difference in our study results and those reported elsewhere 6,13 could be the result of the difference in the method of the RBT used; we based our results on a mRBT, which is more accurate than the basic RBT when testing small ruminants.…”
contrasting
confidence: 74%
“…16 Noteworthy, slightly more positive cases were detected by the iELISA than the mRBT, a finding that differed from several studies. 6,13 In most of the latter studies, as well as our study, the iELISA kit used is a qualitative test that detects only IgG, whereas the RBT kit detects IgM, IgG, and IgA qualitatively. 3 Also, the basic RBT is extremely sensitive but heterospecific 16 ; infection caused by bacteria such as Vibrio cholerae, Yersinia enterocolitica 0:9, Pasteurella spp., Salmonella spp., or some other members of the Brucellaceae family could give more false-positive results in RBT than in the iELISA, a test that may eliminate heterospecific agglutination.…”
mentioning
confidence: 59%
See 3 more Smart Citations